Etiology and management of storage rot of ginger in Himachal Pradesh - DOHROO, N.P. (Indian Phytopathology, 2002)
Pythium ultimum, Fusarium oxysporum and Verticillium chlamydosporium were found associated with storage rot of ginger. The disease was noticed in storage pits from January, which reached its maximum intensity in April at IS.SoC temperature and 67.S per cent relative humidity. Studies on the effect of pre-storage treatments on storage rot of ginger revealed that the pre-storage treatment with Topsin-M and Bavistin each at 0.2 per cent concentration for 60 minutes reduced incidence of storage rot, loss in rhizome weight, surface shriveUing sprouting of ginger and increased the recovery of the rhizomes.